Decolorization of hair dye by lignocellulosic waste materials from contaminated waters - Zahir, Habib; Naidoo, Michelle; Kostadinova, Rada-Mayya; Ortiz, Karla A.; Sun-Kou, Rosario; Navarro, Abel E. (Frontiers in Environmental Science, 2014)
Basic yellow 57 (BY57) was chosen as a model hair dye due to its prevalence in cosmetics wastewaters. This study proposes the use of lignocellulosic materials like spent tea leaves of peppermint (PM), chai tea (CT) and chamomile (CM) as raw adsorbents for the removal of BY57 from contaminated solutions. Batch adsorption experiments were carried out at room temperature to achieve the maximum adsorption capacity. Results indicate that the highest removal is achieved at pH 6 – 8, with a minimum adsorbent mass of 75 mg and in the absence of salinity, crowding agents and heavy metals. Adsorption equilibria were modeled according to the Langmuir and Freundlich isotherm theories and reported the following trend: PM>CT>CM, reaching qmax values of 105, 80, and 38 mg of dye per gram of adsorbent, respectively. Desorption experiments showed that diluted solution of HCl is able to desorb the up to 80% of the dye and recover the adsorbent to be used in consecutive cycles. Finally, the adsorbents were characterized by Scanning electron microscopy, indicating that the adsorbents have a porous and heterogeneous surface, showing pockets and protrusions that are potential adsorption sites for the dye.